IOT based monitoring system for oyster mushroom farming Pondok Seri Permai Pasir Putih Kelantan / Muhd Azhar Zainol ... [et al.] - Zainol, Muhd Azhar; Sh Abdul Nasir, Sh Mohd Firdaus; Abdullah, Nor Suhada; Koay, Mei Hyie; Mohd Halidi, Siti Nur Amalina; Ismail, Hazimi; Leiahs, Lesairuamin (2021)
In Malaysia, many farmers depend upon the traditional agricultural practices. Adapting modern agricultural technology plays an important role in improving overall efficiency as well as yield production. In modern agriculture, the Internet of Things (IoT) connects farmers to their farm via the sensors so that they can easily monitor the real-time conditions of their farm from anywhere. Oyster Mushroom is a widely cultivated crop among Malaysian farmers. Although being the most consumed and cultivated crop, it is still overshadowed by the traditional cultivation approach which results in low productivity, high manpower efficiency, more effort and cost. This work aims to develop a monitoring system to monitor the environmental conditions of a mushroom farm. It enables users to monitor crucial factors such as temperature, humidity, moisture, light intensity on a mushroom farm through the end devices. Oyster Mushrooms require optimum temperature between 26°C to 29°C and humidity between 85% to 95% and carbon dioxide level not more than 600 ppm. Sensors are placed on fixed locations and spots of the farm. The sensors measure the parameter status which is transmitted to the remote monitoring station via a low power Node MCU. Obtained data is stored in a cloud platform. The codes for the controller are written in the Arduino programming language, debugged, compiled, and burnt into the microcontroller using the Arduino integrated development environment. The result shows successful monitoring of environmental conditions accessing the internet from anywhere. It minimizes human efforts and automates production, which could be beneficial to Malaysian farmers.